Heteronemin and tetrac derivatives suppress non-small cell lung cancer growth via ERK1/2 inhibition. (March 2022) - Chung, Cheng-Chin; Huang, Tung-Yung; Chu, Hung-Ru; De Luca, Roberto; Candelotti, Elena; Huang, Chi-Hung; Yang, Yu-Chen S.H.; Incerpi, Sandra; Pedersen, Jens Z.; Lin, Chi-Yu; Huang, Haw-Ming; Lee, Sheng-Yang; et al.
Abstract: The most common cancer, lung cancer, causes deaths worldwide. Most lung cancer patients have non-small cell lung carcinomas (NSCLCs) with a poor prognosis. The chemotherapies frequently cause resistance therefore search for new effective drugs for NSCLC patients is an urgent and essential issue. Deaminated thyroxine, tetraiodothyroacetic acid (tetrac), and its nano-analogue (NDAT) exhibit antiproliferative properties in several types of cancers. On the other hand, the most abundant secondary metabolite in the sponge Hippospongia sp., heteronemin, shows effective cytotoxic activity against different types of cancer cells. In the current study, we investigated the anticancer effects of heteronemin against two NSCLC cell lines, A549 and H1299 cells in vitro . Combined treatment with heteronemin and tetrac derivatives synergistically inhibited cancer cell growth and significantly modulated the ERK1/2 and STAT3 pathways in A549 cells but only ERK1/2 in H1299 cells. The combination treatments induce apoptosis via the caspases pathway in A549 cells but promote cell cycle arrest via CCND1 and PCNA inhibition in H1299 cells. In summary, these results suggest that combined treatment with heteronemin and tetrac derivatives could suppress signal transduction pathways essential for NSCLC cell growth. The synergetic effects can be used potentially as a therapeutic procedure for NSCLC patients. Highlights: Both heteronemin and tetrac derivatives exhibited cytotoxic effects in NSCLCs, and combined treatment enhanced the anti-proliferation. Heteronemin- and tetrac derivative-Inactivated ERK1/2 activities played a role in anti-proliferation in NSCLCs. Heteronemin induced G0/G1 arrest of the cell cycle via inhibiting the expression of CCND1 and PNCA in H1299 cells, while heteronemin induced apoptosis through increasing Caspases activation in A549 cells. Heteronemin or tetrac blocked NSCLC cells migration, and the combined treatment further enhanced the effect.